Pengelolaan Turnitin Di FITK UIN Malang: Kajian Atas Efektivitas Penerapan Scanning Tugas Akhir Untuk Mencegah Plagiarisme - Afwadzi, Benny; Malik, Adam; Salsabiila, Husniyya Safira; Yulanda, Nurul Izhan Pepridel (Ar-Rosikhun: Jurnal Manajemen Pendidikan Islam, 2022)
This article discusses the effectiveness of Turnitin scanning at the Faculty of Tarbiyah and Teacher Training at UIN Maulana Malik Ibrahim Malang which was carried out at the Research and Academic Writing Center (Pusat Penelitian dan Academic Writing, PPAW) on student proposals and thesis. The existence of Turnitin scanning itself is due to seeing the phenomenon of plagiarism among students which until now has been included in the category of concern, so efforts are needed to prevent the negative behavior in the world of education. This article is the result of research that uses a qualitative approach, which is carried out by analyzing the data from Turnitin proposals and thesis for FITK students at PPAW. With purposive sampling method, there are three sample study programs, namely Islamic Religious Education (PAI), Islamic Education Teacher Education (PGMI), and Social Science Education (PIPS). The data analysis in this study uses Miles and Huberman's data analysis techniques, namely data reduction, data presentation, and drawing conclusions. There are two conclusions, first, the Turnitin scanning process at PPAW begins with sending proposals and student thesis through the google form that has been provided previously. When getting the similarity results as determined, the student will be sent a plagiarism-free certificate. However, if they fail, the student will be given information regarding this and sent a scan of Turnitin as revision material. The process from start to finish takes 1-5 working days. For students who fail, the submission of new revisions can be done after seven days. Second, it can be concluded in general that Turnitin scanning in PPAW is effective in tackling plagiarism among students, even though there are various delinquency committed by them, namely reducing or adding letters, changing into images, using inappropriate direct quotations, deleting parts that have high similarity, and sending revisions that are not in accordance with a predetermined schedule. Finally, to be more effective, this study recommends several further policies, namely sending in word form with a few exceptions for pages with image formats, examining all files and changing the color to black, making Turnitin scanned files as manuscripts for proposal seminars and munaqasyah, and lastly, providing training on how to write good scientific papers.